Dominance, Overdominance and Epistasis Condition the Heterosis in Two Heterotic Rice Hybrids - Li, Lanzhi; Lu, Kaiyang; Chen, Zhaoming; Mu, Tongmin; Hu, Zhongli; Li, Xinqi (Genetics (Austin), 2008)
Two recombinant inbred (RI) populations having 194 and 222 lines each, derived, respectively, from a highly heterotic inter- (IJ) and intrasubspecific (II) hybrid, were backcrossed to their respective parents. The RI and two backcross populations along with F1 and its two parents of each hybrid were evaluated for nine important traits, including grain yield and eight other yield-related traits. A total of 76 quantitative trait loci (QTL) for the IJ hybrid and 41 QTL for the II hybrid were detected in the RI population, midparent heterosis of two backcross populations, and two independent sets of data by summation (L1 + L2) and by subtraction (L1 − L2) of two backcross populations (L1 and L2). The variance explained by each QTL ranged from 2.6 to 58.3%. In the IJ hybrid, 42% (32) of the QTL showed an additive effect, 32% (24) a partial-to-complete dominant effect, and 26% (20) an overdominant effect. In the II hybrid, 32% (13) of the QTL demonstrated an additive effect, 29% (12) a partial-to-complete dominant effect, and 39% (16) an overdominant effect. There were 195 digenic interactions detected in the IJ hybrid and 328 in the II hybrid. The variance explained by each digenic interaction ranged from 2.0 to 14.9%. These results suggest that the heterosis in these two hybrids is attributable to the orchestrated outcome of partial-to-complete dominance, overdominance, and epistasis.